ESTABLISHMENT OF SOVIET POWER IN TURKESTAN. ARRANGEMENTS TAKEN BY THE SOVIET AUTHORITIES IN UZBEKISTAN AND THEIR COLONIAL ESSENCE - political , repression; Esonova , Feruza (Effective scientific journals, 2025)
This article analyzes the process of the establishment of Soviet power in Turkestan, its political, social and economic factors on a scientific basis. The main focus was on measures taken by Soviet authorities between 1917 and 1924, in particular, the policy of national-state delimitation, centralization of the management system, land-water reform, industrial and agricultural reorganization. The article reveals that although the policy of Soviet power on the territory of Uzbekistan is decorated externally with the slogans “modernization” and “social equality”, it actually has a colonial essence. There is also a critical analysis of the limitation of the political rights of the local population, the persecution of the National intelligentsia and the management system that served the interests of the center. Based on the principles of historicism and objectivity, the study serves to highlight an important and complex period of Turkestan history.